Forecasting the Term Structure of Philippine Interest Rates Using the Dynamic Nelson-Siegel Model - Fernandez, Proceso L, Jr (Archīum Ateneo, 2017)
The three-factor Nelson-Siegel model is a widely used model for forecasting the term structure of interest rates. Several extensions have recently been proposed. Even for the original model, different methods of treating the parameters have been shown. Ultimately, what works best depends on the data used to estimate the parameters. In this paper, the original three-factor model with fixed shape parameter was applied to forecast the term structure using market data from the Philippines. Instead of giving a pre-determined model for the latent factors, the best time series model for them was searched using standard statistical tools. Based on the historical data, the best model for each latent factor is of the form ARMA(p,q)+eGARCH(1,1). The dependence structure of these parameters was considered in generating their future values. This was carried out by finding the joint distribution of the residuals via appropriate copula. Results show that forecast of interest rates for different tenors is reliable up to the near future. For an active market, this is good enough since the models for the parameters can be adjusted as new information comes in.